2015
DOI: 10.1016/j.neuroscience.2015.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia reduces functional expression of astrocytic Kir4.1 channels and glial glutamate uptake

Abstract: Diabetics are at risk for a number of serious health complications including an increased incidence of epilepsy and poorer recovery after ischemic stroke. Astrocytes play a critical role in protecting neurons by maintaining extracellular homeostasis and preventing neurotoxicity through glutamate uptake and potassium buffering. These functions are aided by the presence of potassium channels, such as Kir4.1 inwardly rectifying potassium channels, in the membranes of astrocytic glial cells. The purpose of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Astrocytes were seeded in 24 culture flasks (10 6 cells/flask) and five 24-well plates (10 5 cells/well) for examination of intracellular and extracellular lactate levels, respectively. Cells were washed once with HBSS 24 h after seeding, and the culture medium was replaced by fresh DMEM containing 5.5 mM glucose for the control group or 25 mM for the high-glucose group (31)(32)(33).…”
Section: Methodsmentioning
confidence: 99%
“…Astrocytes were seeded in 24 culture flasks (10 6 cells/flask) and five 24-well plates (10 5 cells/well) for examination of intracellular and extracellular lactate levels, respectively. Cells were washed once with HBSS 24 h after seeding, and the culture medium was replaced by fresh DMEM containing 5.5 mM glucose for the control group or 25 mM for the high-glucose group (31)(32)(33).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in humans, seizure susceptibility is increased by hyperosmolarity, hyponatremia and hyperglycemia, caused by both type 1 and type 2 diabetes [24,25]. In cell culture, we have shown that Kir4.1 mRNA and protein levels are downregulated in astrocytes cultured in high glucose medium (simulating uncontrolled diabetes) and down-regulation is associated with impaired K + uptake and glutamate clearance by these astrocytes [26].…”
Section: Introductionmentioning
confidence: 91%
“…In other words, there is a disruption of the harmonic interaction between astrocytes (glycolysis, lactate release, and glutamate uptake) and neurons (lactate uptake and its use as a fuel source in oxidative metabolism). But, it must be emphasized that the interactions between astrocytes and neurons involve not only glucose/lactate metabolism, but also neuroprotective mechanisms similar than that triggered during ischemia (Gouix et al, 2014), chronic hyperglycemia (Rivera-Aponte et al, 2015), and traumatic brain injury (Crupi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%